Non-contact human respiratory rate measurement based on two-level fusions of video and FMCW radar information - Song, Rencheng; Ren, Cong; Cheng, Juan; Li, Chang; Yang, Xuezhi (Measurement : journal of the International Measurement Confederation, 2023)
In this paper, we propose a robust respiratory rate (RR) measurement method using a two-level fusion of video and FMCW (frequency modulated continuous wave) radar information. Specifically, the video pixel displacement signals and the radar phase variation signals are extracted independently in shoulders and chest regions, which are then denoised by the serial-CEEMDAN (SCEEMDAN) method to obtain the corresponding single modal RR values. Next, at the feature level, the multivariate singular spectrum analysis (MSSA) is employed to extract the shared respiratory components in the video and radar modalities. Finally, at the decision level, we calculate the target RR value based on a signal-to-noise ratio (SNR) weighting of all single-modality and MSSA results. The proposed two-level fusion method is evaluated on a self-collected dataset, which includes 15 healthy subjects acting five challenging activities. The experimental results show that the proposed fusion method significantly outperform that of the single modality. •The serial-CEEMDAN method is introduced to denoise the respiratory signals.•A two-level fusion method is proposed for motion robust respiratory measurements.•Experimental results in challenging scenarios verify the benefits of the method.